Tactile perception and manual dexterity in computer users - Tremblay, François; Mireault, Annie-Claude; Létourneau, Julie; Pierrat, Audrey; Bourrassa, Shannon (Somatosensory & motor research, 2002)
Recent studies suggest that sensory input generated during highly repetitive tasks can degrade the sensory representation of the hand and eventually lead to sensory and motor problems. In this study, we investigated whether early changes in tactile perception and manual dexterity could be detected in persons exposed to computer tasks. Performance in tests designed to assess tactile perception (grating orientation task for spatial acuity and roughness discrimination) and manual dexterity (grooved pegboard test) was compared between two groups of healthy individuals, matched for age, gender, and experience, who differed in terms of computer habits. One group consisted of frequent users (FU, > 2 h/day, n = 36) and the other of non or occasional users (OU, < 2 h/day, n = 28). Comparison of performance between groups with subjects sorted by gender revealed significant differences ( t -test, p < 0.05) in female, but not male, participants. Grating resolution thresholds at the tip on the second and fifth digits were, on average, 40% higher in female FU ( n = 13) than in female OU ( n = 10) and performance scores on the dexterity test were significantly higher for the left hand. The results of this study indicate that early signs of deterioration in hand function can be present in persons constantly exposed to computer tasks and that these signs are more readily apparent in women than in men. The loss of tactile spatial acuity found in female FU possibly reflect an early consequence of the degraded sensory representation of the hand resulting from constant repetitions of fine motor tasks.